COURTYARD ENHANCES NATURAL VENTILATION AND DAYLIGHTING IN BUILDINGS IN NIGERIA - Kenneth, Nwifa Le-ema; Napoleon, Prof Imaah Ono (International Journal of Environmental Sciences, 2019)
Purpose: This paper examines how courtyards enhance natural ventilation and day lighting in buildings. Methodology: The method adopted for the research paper is the secondary methods of sources of information which includes review of existing literatures (papers) written by others, with emphasis on ventilation and day lighting. This paper is to encourage the incorporation of courtyard design in buildings as a means of enhancing ventilation and day lighting as to the reliance on mechanical means of using artificial cooling systems such as air conditioners which is not eco-friendly and it is more expensive and causes high energy consumption in buildings which is a major factor to climate change. Results: The incorporation of a courtyard into a building form offers a microclimatic buffer zone between the outdoor and indoor environments of the building, offers a substantial potential for utilizing passive strategies for indoor thermal comfort. A courtyard presents a greater flexibility in promoting larger areas of internal passive zones, which can benefits from natural ventilation and daylight. Unique contribution to theory, practice and policy: Courtyard should be encourage in our designs as architects to save energy, reduce cost of construction through the installation of artificial cooling systems thus encouraging eco-friendly buildings and taking full advantage of the therapeutic, cooling, day-light and natural ventilation that courtyard provides